Rotatable Smart TinyLab, a platform for testing integrated façades and indoor climate. Issue 1 (1st September 2022) - Mohammadi, S; Weersink, A; ′t Ende, J van; Struck, C
Abstract: The new Smart TinyLab (STL) for system integration in the building industry is a lab where building partners and construction-related companies can develop, test, validate and demonstrate their products in practice to be as energy-efficient as possible to contribute to formulated CO2 emission reduction targets. STL is located near the Saxion University of Applied Sciences in Enschede and has been operationalized since the spring of 2021. In the lab, one can simulate and assess quantitatively the effect of building products, HVAC components, smart technologies, user-related aspects and the outdoor climate on energy consumption and indoor climate conditions. The lab allows the comparison between theoretical and practical characteristics and energy consumption figures. Together with partners from the construction industry, innovative products, devices and systems in a simulation and field test environment have been tested and validated. During STL′s start-up phase other tiny twin-labs with outdoor setups in Europe were compared. Turning the lab in its entirety to face or be averted from direct sunlight makes STL rather unique in its kind.